2005
DOI: 10.1210/me.2004-0471
|View full text |Cite
|
Sign up to set email alerts
|

α1-Adrenergic Receptor Antagonists: Novel Therapy for Pituitary Adenomas

Abstract: Pituitary tumors are common and cause considerable morbidity due to local invasion and altered hormone secretion. Doxazosin (dox), a selective alpha(1)-adrenergic receptor antagonist, used to treat hypertension, also inhibits prostate cancer cell proliferation. We examined the effects of dox on murine and human pituitary tumor cell proliferation in vitro and in vivo. dox treatment inhibited proliferation of murine pituitary tumor cells, induced G(0)-G(1) cell cycle arrest, and reduced phosphorylated retinoblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 31 publications
5
28
0
1
Order By: Relevance
“…31 Several other reports showed that doxazosin downregulated NF-B signaling and induced apoptosis in some types of cells. [35][36][37] These findings are not inconsistent with our results of inhibition of PKD and AP2␣ phosphorylation by doxazosin.…”
Section: Discussionsupporting
confidence: 72%
“…31 Several other reports showed that doxazosin downregulated NF-B signaling and induced apoptosis in some types of cells. [35][36][37] These findings are not inconsistent with our results of inhibition of PKD and AP2␣ phosphorylation by doxazosin.…”
Section: Discussionsupporting
confidence: 72%
“…Alpha 1 adrenergic receptor antagonists have been suggested as a novel therapy for pituitary adenomas (Fernando & Heaney 2005). In murine pituitary tumor cells, doxazosin (Cardura, Cardura XL) reduced phosphorylated retinoblastoma protein levels and induced G0-G1 cell cycle arrest with decreased tumor growth and reduced plasma ACTH levels (Fernando & Heaney 2005).…”
Section: Alpha 1 Adrenergic Receptor Antagonistsmentioning
confidence: 99%
“…In murine pituitary tumor cells, doxazosin (Cardura, Cardura XL) reduced phosphorylated retinoblastoma protein levels and induced G0-G1 cell cycle arrest with decreased tumor growth and reduced plasma ACTH levels (Fernando & Heaney 2005). Further research is required to support the observations.…”
Section: Alpha 1 Adrenergic Receptor Antagonistsmentioning
confidence: 99%
“…Doxazosin-mediated antiproliferative effects have been described in prostate tumors, where increased prostate cancer cell apoptosis and decreased serum prostate-specific antigen levels were reported in patients with prostate cancer. Treatment of murine pituitary tumor corticotroph (AtT20) and gonadotroph (LβT 2 , and αT 3 ) tumor cells with doxazosin 10–30 µ M in vitro inhibited cell proliferation, increased apoptosis and slowed in vivo tumor development [29]. However, α 1 -adrenergic receptor expression was not detectable in several of the pituitary tumor cell lines, and cotreatment of the pituitary tumor cells with the noncompetitive α-adrenoreceptor blocker phenoxy benzamine and doxazosin together did not abrogate doxazosin-mediated apoptosis.…”
Section: Quinazoline-based α-Adrenergic Receptor Antagonistsmentioning
confidence: 99%